Incidence and risk factors for term low birth weight babies in a tertiary care hospital in Kerala - Jacob, Sheela; Jacob, Ancy T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Birth weight of <2.5 kg at birth is considered low birth weight and impacts the individual’s health during their adult life. Babies are born with low birth weight, both in term and preterm deliveries. This study aims to find the incidence of term low birth weight babies (TLBW) and the maternal risk factors associated with the same. Methods: This case-control study was conducted on 166 pregnant women who had term live births during the study period July 2019 to December 2020. Inclusion criteria: Women with a live singleton TLBW (<2.5 kg) - cases (63) and normal birth weight babies - controls (103). Control group selection was 1:2 proportion as per the cases. Exclusion criteria consisted of women with multiple gestations. Binary and categorical variables were presented using counts and percentages. Independent sample t-test was used to compare two continuous variables, and the chi-square test/Fisher’s exact test was used to find the association of categorical variables. Results: 1344 live births were reported during the study period, of which 63 cases were TLBW babies with an incidence of 4.68%. Among the baseline parameters, significant difference was observed only in body mass index (BMI). After assessing the common risk factors like anemia, urinary tract infection (UTI), genital tract infection, gestational diabetes mellitus (GDM), and gestational hypertension, only hypothyroidism showed significant association with TLBW (OR: 2.240, 95% CI:0.98-5.13, p=0.006). Conclusions: The incidence of TLBW babies was 4.68%, which is low compared with other studies. Hypothyroidism shows significant association with TLBW in this study which was not observed in previous literature.